2002
DOI: 10.1128/mcb.22.8.2687-2702.2002
|View full text |Cite
|
Sign up to set email alerts
|

Sp100 Interacts with ETS-1 and Stimulates Its Transcriptional Activity

Abstract: The cell nucleus is highly organized into distinct domains that spatially separate physiological processes. One of these domains, the Sp100-promyelocytic leukemia protein nuclear body (NB), is implicated in pathological processes, such as cancer and viral infection, yet its functions remain poorly understood. We show here that Sp100 interacts physically and functionally with ETS-1 and that NB morphology is affected by ETS-1. ETS-1 is a member of the ets family of transcription factors, which are key mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 72 publications
3
51
0
Order By: Relevance
“…For example, both proteins have been shown to activate a number of genes coding for extracellular matrix-degrading proteases and, therefore, are assumed to be involved in the acquisition of cellular invasiveness ( [27] and references therein). Recently, Ets1 was found to be associated also with the regulation of the promyelocytic leukaemia protein oncogenic domains ('PODs') that seem to be deregulated in invasive tumours [56]. In the present study, combined with the results we have published previously [20], we provide evidence suggesting that these Ets factors also participate in the regulation of the expression of the (breast) tumour-promoting protein, PTHrP.…”
Section: Discussionsupporting
confidence: 72%
“…For example, both proteins have been shown to activate a number of genes coding for extracellular matrix-degrading proteases and, therefore, are assumed to be involved in the acquisition of cellular invasiveness ( [27] and references therein). Recently, Ets1 was found to be associated also with the regulation of the promyelocytic leukaemia protein oncogenic domains ('PODs') that seem to be deregulated in invasive tumours [56]. In the present study, combined with the results we have published previously [20], we provide evidence suggesting that these Ets factors also participate in the regulation of the expression of the (breast) tumour-promoting protein, PTHrP.…”
Section: Discussionsupporting
confidence: 72%
“…It has also been hypothesized that the nuclear body serves as a dynamic nuclear depot (Negorev et al, 2001), providing a mechanism to control the activity of the proteins that localize to the NB. Although ETS1 does colocalize with SP100 in the NB, the NB does not appear to provide a significant storage depot for ETS1 relative to total ETS1 protein, as both previous indirect immunofluorescence analysis (Wasylyk et al, 2002) and the studies described here show ETS1 is found throughout the entire nucleus. Further experimentation is needed to determine if the functional interaction between ETS1 and SP100 is geographically restricted to the NB.…”
Section: Discussionmentioning
confidence: 49%
“…SP100 has been shown to interact with heterochromatin protein 1 (HP1), which functions as a transcriptional repressor (Seeler et al, 1998), and SP100 acts as repressor of transcription when tethered to DNA (Lehming et al, 1998;Seeler et al, 1998;Bloch et al, 1999). However, SP100 and ETS1 have recently been reported to coactivate the MMP3 (stromelysin) promoter as well as a heterologous promoter containing multimerized EBS (Wasylyk et al, 2002). Although no direct evidence was provided, it was proposed that ETS1 and SP100 are able to form a complex on the EBS present on the MMP3 promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another gene, SP100, has been decribed to be a modulator of Ets1 activity (Wasylyk et al, 2002;Yordy et al, 2004). SP100 colocalizes with PML in nuclear bodies (Salomoni and Pandolfi, 2002) whose number can be regulated by Ets1 (Wasylyk et al, 2002;Yordy et al, 2004).…”
Section: Sipa Interferes With Ets1 Protein Synthesis and Stabilitymentioning
confidence: 99%